PERBANDINGAN PENGARUH SUKU BUNGA DAN INFLASI TERHADAP KREDIT DAN PEMBIAYAAN (Studi Kasus pada Bank Umum Konvensional dan Bank Umum Syariah periode 2011-2015) - Putra, Hasannudin Nursalim; Aryq, Irnin Miladyan; Mufidah, Lilik Jazilatul (Fakultas Ekonomi, UIN Maliki Malang, 2016)
Inflationary pressures that often time there was a can shake economy the state, to face inflationarypressures one of the efforts of the country to control the inflation is by issuing policy interest rate by theIndonesia bank as central financial policy monetary and fiscal. The banks have the role of to control the rateinflation. The interest rate that set by the bank will affect the level distribution credit of bank conventional andfinancing of sharia bank. For that researchers want to see the influence of direct and indirect interest rates tocredit and financingand inflation as variable intervening. The kind of research is quantitative with the sampleof six general Sharia Bank and the generalconventional bank in Indonesia period 2011 until 2015 taken withpurposive sampling. Themethod is path analysis. Based onsignificant test, the first significant test has resultthat interest rates significant of inflation. Thesecond significant testhas results that the interest rate notsignificant on the distribution credit and financing. The third significant test has result that inflation is notsignificant to distribution credit and financing. So this is can concluded that inflation will not be variableintervening for the distribution credit and financing.